Clinical and molecular study of a case of severe radio-sensitivity - Ocolotobiche, Eliana Evelina (2019)
A case of a patient with a breast intraductal tumor is presented The patient underwent surgical quadrantectomy and axillary lymph node dissection and subsequently received Anthracycline treatment and D radiotherapy following a standard fractionation protocol This case was characterized by the development of grade III dermal toxicity some associated genetic polymorphisms and DNA damage were analyzed We concluded that radiotoxicity is a multifactorial phenotype that should be addressed in a broader context considering not only intrinsic variables but also criteria such as breast size body mass index and concomitant treatments among others